Aplikasi TikTok dengan Model PBLA untuk Meningkatkan Kemampuan Argumentasi Peserta Didik pada Konsep Pengukuran Fisika - Prastiwi, Ayu Nita; Fatmaryanti, Siska Desy; Akhdinirwanto, Raden Wakhid (UNIB Press, 2024)
This study aims to develop learning media by utilizing the TikTok application with the PBLA model on the topic of measurement and to determine the enhancement of participants' argumentation skills. This study is a Research and Development (R&D) study employing the ADDIE development procedure (Analyze, Design, Development, Implementation, and Evaluation). The research subjects were 36 students from class X-E of MAN Purworejo in the academic year 2023/2024. The research instruments used were validation sheets, participant response questionnaires, observation sheets, pretest-posttest questions, and learning implementation sheets. The data analysis results show that the physics instructional video media utilizing the TikTok application with the PBLA model meets the